(untitled) (Journal of Renal and Hepatic Disorders, 2019)
Proteolysis is an irreversible post-translational modification that regulates protein function and signal transduction. This includes remodelling of the extracellular matrix, release of membrane-bound cytokines and receptor ectodomains, as well as the initiation of intracellular signalling cues. Members of the adamalysin protease subfamily, in particular the ADAM (a disintegrin and metalloprotease) and ADAMTS (the ADAM containing thrombospondin motif) families, are involved in these processes. This review presents an overview of how ADAM and ADAMTS proteins are involved in liver physiology and pathophysiology.